TIPOLOGI INSTALASI MILITER JEPANG DI KOTA PALEMBANG, SUMATERA SELATAN - Nes, Muhammad Riyad (Siddhayatra, 2018)
The military installation is a defense building that is specifically established,strengthened and closed, serves to protect an area or army from enemy attacks. Thepurpose of this paper is to find out the shape and function of military installations in the cityof Palembang. This research method consists of the stages of data collection and specialanalysis using a spatial approach. The results of this study indicate that militaryinstallations in the city of Palembang have several forms, namely irregular shapes, U,rectangular, rectangular and circular / circular shapes. The function of the militaryinstallation is to maintain the oil mining area in the city of Palembang and as a base ofdefense and a place to spy on the enemy.